Spain : Financial Sector Assessment Program; Detailed Assessment of the CPSS-IOSCO Recommendations for the Securities Settlement Systems. (IMF Staff Country Reports; Country Report, 2006)
This report describes the assessment of the securities clearance and settlement system in Spain, based on the Committee on Payment and Settlement Systems (CPSS)-International Organization of Securities Commissions' (IOSCO) Recommendations for Securities Settlement Systems. It is performed using the CPSS/IOSCO assessment methodology, and assesses the Management Company for Securities Registry, Clearance and Settlement, which operates under the commercial name of Iberclear, a corporation of the Securities Clearance and Settlement Service, SCLV, and the Central Public Registry.